Combined Tibial Plateau Levelling Osteotomy and Tibial Tuberosity Transposition: An Ex Vivo Mechanical Study - Birks, Ryan R.; Kowaleski, Michael P. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives The purpose of this study is to compare the load at failure and mode of failure between (1) tibial plateau levelling osteotomy (TPLO) and combined TPLO and tibial tuberosity transposition (TPLO-TTT) (Phase I) and (2) TPLO-TTT and tibial tuberosity transposition (TTT) (Phase II).Methods Seven pairs of cadaveric tibiae were tested in each of the Phase I (TPLO vs. TPLO-TTT) and Phase II (TPLO-TTT vs. TTT) experiments. One limb of each pair was randomly assigned to one of two groups for each experimental phase. A tensile force was applied to the patellar ligament until construct failure occurred.Results There was a significant difference in mean load at failure between TPLO (2092.8 N) and TPLO-TTT (1067.8 N), p = 0.004. All TPLO constructs failed by fracture of the tibial crest. The TPLO-TTT constructs failed by cranial displacement of the distal tibial crest. Additionally, the tibial plateau was displaced in the majority of limbs. There was a significant difference in mean load at failure between TPLO-TTT (1157.6 N) and TTT (1394.0 N), p = 0.025. The TTT constructs demonstrated a similar mode of failure as TPLO-TTT.Clinical Significance Although ex vivo mechanical testing does not replicate the postoperative clinical scenario, these results demonstrate reduced construct strength of the combined TPLO-TTT technique compared with TPLO or TTT alone. When performing TPLO-TTT, meticulous technique and implants of adequate strength must be employed to create a robust construct and minimize postoperative tibial crest fixation failure.
Keywords: mechanical testing; patellar luxation; cranial cruciate ligament disease